Analisis Perencanaan Sumber Daya Manusia di PT Aerofood Acs Unit Denpasar - Danella, Sangiang Ruth; Satriawan, I Ketut; Sadyasmara, Cokorda Anom Bayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 4 (2020): DesemberDO - 10.24843/JRMA.2020.v08.i04.p14, 2020)
The role of human resource management is the main key of transformation the management of a company to gain a competitive advantage. The purposes of this research were to analyze the condition and the demand and supply of human resources for the next two years at PT Aerofood ACS Denpasar unit. The methods used to analyze human resource demand data were Trend Analysis and Delphi technique along with the inventory skill to analyze the human resource supply data. Trend analysis method used to increases the demand for human resource for the next two years, while the Delphi technique used to sees the condition of the company for the last 4 years. The inventory skill method used to analyze the offering position for internal and external employees for the next two years. The condition of human resource in the company during for the latest year is good, because the percentage of employee turnover is 0.57 percent and the employee retention rate is 99.43 percent. The percentage of absence level for back office employees was only 7.07 percent and 8.46 percent for operational employees. The projection result of human resource demands for the next two years, there will be a reduction in the number of permanent workers by 17 people in the first year and a further reduction of 34 employees in the second year, this is due to the absence of permanent employment designation for the last four years. The contract employees have decreased 17 employees at the first year due to force majeure and an increase of 55 people in the second year when the amount of production is normal, especially for operational workforce. Outsourcing labor and daily workers are not needed in the first year but will likely be needed further. Keywords : Aerofood ACS, human resource, trend analysis, Delphi technique, skill inventory